Pengaruh Store Atmosphere, Promosi dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada PT. SIP Soetta Probolinggo - M Ali Wafa; Tatik Amani; Setyani Hidayati (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at PT. Roda Sakti Surya Megah City of Probolinggo with the aim of the research to be achieved is to determine the effect of shop atmosphere, promotion and service quality on purchasing decisions partially at PT. Roda Sakti Surya Megah, City of Probolinggo. The population in this study are all consumers of PT. Roda Sakti Surya Megah, City of Probolinggo, with a sample taken of 49 respondents with a sampling technique that is saturated sample. The type of research used in this research is descriptive quantitative research, the variables used are Store Atmosphere, Promotion, Service Quality and Purchasing Decisions. The method of data analysis from the results of this study is a quantitative descriptive method using statistics in the form of instrument test, validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple regression analysis, coefficient of determination, multiple correlation hypothesis , and hypothesis testing. The results of the study are shown by the results of simultaneous hypothetical tests Fcount > Ftable (23.315 > 2.81) (sig. 0.00 <0.05) then H0 is rejected. That is, there is a significant influence between Store Atmosphere (X1), Promotion (X2) and Quality of Service (X3) simultaneously on purchasing decisions (Y).